Epidemics of signification and global health policy: From the end of AIDS to the end of scale-up of the global AIDS response - Richard Parker (Taylor & Francis Group, 2024)
ABSTRACTOver the past four and a half decades, the history of the HIV and AIDS pandemic has gone through a number of different phases, which can be thought of as distinct waves in terms of the social and political response that the pandemic has generated. Over the course of this history, there have been important battles over the meanings and interpretations that the response to the pandemic has produced. But especially over the past decade, there seems to be a growing disconnect between claims of success made by many global health agencies and policymakers and the empirical reality that these claims cover up. This commentary argues that the 'scale-up' of the response to the pandemic has essentially come to an end and emphasises the importance of a more honest policy debate about the current state of the global HIV response. It argues that this requires us to think critically about the ways in which this response has developed historically, to recognise the significant advances achieved in recent decades, but also to acknowledge the important crossroads that it has reached in the mid-2020s, in order to better define the directions that it should take in the future.